Abordagem genética e multivariada na performance agronômica de genótipos de soja oriundos de diferentes genealogias - Gomez, Guillermo Marcelo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The objectives of the present study were to: (i) evaluate the genotypic performances of 45 soybean genotypes with the future finality of recommendation of varieties for the State of São Paulo, Brazil; (ii) determine the stability and adaptability of the 45 genotypes utilizing the Wricke’s ecovalence, AMMI (additive main effects and multiplicative interaction analysis), GGE-Biplot and MHPRVG (harmonic mean of the relative performance of genotypic values) methods; (iii) evaluate the phenotypic, genotypic and environmental correlations among the traits of 45 genotypes in three environments. The exploration of genotype-byenvironment interaction (GEI) allowed the identification of 21 genotypes with high mean grain yield, representing different relative maturity groups and stability levels to the environments. This group was subdivided by crop cycle, in which the genotypes 18, 36, 20, 34 and 33 were early cycles (108 days – 125 days), while genotypes 11, 22, 44 (CD 219), 24, 23, 14, 32, 1, 12, 39, 30, 38, 7 and 26 were medium cycles (126 days – 135 days) and genotypes 25 and 37 were late cycles (≥ 136 days). The interpretations obtained from the ecovalence, AMMI and GGE-biplot methods were more similar than the interpretations obtained from the MHPRVG method. This was due to the method’s properties, which give more weight to grain yield and little weight to the adaptability and stability parameters. The genotypic and environmental correlations among traits enhanced the interpretations of the genotype x environmental interactions

Os objetivos do presente estudo foram: (i) avaliar as performances genotípicas de 45 genótipos de soja com a finalidade futura de recomendação de cultivares para o Estado de São Paulo, Brasil, (ii) determinar a estabilidade e a adaptabilidade dos 45 genótipos por meio dos métodos de ecovalência de Wricke, AMMI (efeitos principais aditivos e análise da interação multiplicativa), GGE-Biplot e MHPRVG (média harmônica da performance relativa do valore genotípico), (iii) avaliar as correlações fenotípicas, genotípicas e ambientais entre as características de 45 genótipos em três ambientes. A exploração da interação genótipo x ambiente (IGE) permitiu a identificação de 21 genótipos com altos rendimentos de grãos, de diferentes grupos de maturidade relativa e níveis de estabilidade para os ambientes. Esse grupo foi subdividido por ciclo de cultivo, genótipos de ciclos curtos (108 dias - 125 dias) 18, 36, 20, 34 e 33, genótipos de ciclos médios (126 dias - 135 dias) 11, 22, 44 (CD 219), 24, 23, 14, 32, 1, 12, 39, 30, 38, 7 e 26 e genótipos de ciclos tardios (≥ 136 dias) 25 e 37. Interpretações similares foram obtidas dos métodos de ecovalência, AMMI e GGE-Biplot. Enquanto que as interpretações obtidas da análise MHPRVG foram diferentes. Isso foi devido às propriedades do método, que da maior peso à produtividade de grãos e pouco peso aos estatísticos de adaptabilidade e estabilidade. A análise de correlações genéticas e ambientais entre as variáveis dos genótipos e ambientes avaliados reforçou as interpretações da exploração da interação genótipos x ambientes
Keywords: Soja; Estabilidade; Genetica vegetal; Desempenho; Soja - Adaptação; Stability